2020
DOI: 10.3390/nu12030834
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant and Anti-Inflammatory Properties of Anacardium occidentale L. Cashew Nuts in a Mouse Model of Colitis

Abstract: Background: Anacardium occidentale L. is a tropical plant used for the treatment of inflammatory diseases. The goal of the present work was to investigate the anti-inflammatory and anti-oxidant potential of oral administration of cashew nuts (from Anacardium occidentale L.) in a mouse model of colitis. Methods: Induction of colitis was performed by intrarectally injection of dinitrobenzene sulfonic acid (DNBS). Cashew nuts were administered daily orally (100 mg/kg) in DNBS-injected mice. Results: Four days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 42 publications
3
92
0
Order By: Relevance
“…Table 1 reports the nutritional profile of cashew kernel samples from Ivory Coast (Africa). In agreement with the chemical composition of West Africa cashew [ 15 ], cashews contain a high proportion of lipid (44.19%), followed by carbohydrate (35.43%) expressed as sum of soluble sugars and fiber and protein (22.46%). The total phenolic content, expressed as mg/100 g of sample, was higher (80.01) compared to what was reported in our previous work for West Africa cashews (69.64) [ 22 ].…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…Table 1 reports the nutritional profile of cashew kernel samples from Ivory Coast (Africa). In agreement with the chemical composition of West Africa cashew [ 15 ], cashews contain a high proportion of lipid (44.19%), followed by carbohydrate (35.43%) expressed as sum of soluble sugars and fiber and protein (22.46%). The total phenolic content, expressed as mg/100 g of sample, was higher (80.01) compared to what was reported in our previous work for West Africa cashews (69.64) [ 22 ].…”
Section: Resultssupporting
confidence: 64%
“…Well-known antioxidants such as quercetin, curcumin, and vitamin C protect against I/R injury [ 30 , 31 ], proposing that natural sources of antioxidants may be useful to treat this issue. Previous studies from our laboratory showed the antioxidant properties of cashew nuts in experimental model of colitis and osteoarthritis [ 15 , 22 ]. In particular, these studies showed cashew nuts’ ability to alleviate the clinical signs, pain perception, histological damage, and molecular mediators involved in these diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations